Ensaios sobre determinantes socioeconômicos da proteção e engajamento ambiental - Castro, Andressa Porto (2023)
The thesis is divided into three essays, whose main theme is the study of the socio-economic determinants associated with individuals' perception and environmental engagement. Essay 1 proposes a cross-country analysis to examine the factors associated with environmental protection when individuals are faced with the choice between environmental protection or economic growth. This study analyzes, using a multilevel regression model, both the individual socioeconomic factors that influence the choice for environmental protection, as well as the contextual aspects of the countries, such as GDP per capita, income inequality and level of democracy that affect this choice. The results suggest that both individual and contextual factors influence the choice for environmental protection. In general, the population of democratic countries and countries with higher per capita GDP are more likely to prefer to protect the environment. The second essay seeks to analyze the environmental perception of Brazilians, the objective is to ascertain the presence of an environmental gender gap concomitantly with the financial status of individuals. To capture the difference in environmental perception between men and women, the Oaxaca-Blinder decomposition method for non-linear models was employed. The results of this study show that, in general, women usually show more environmental concern when compared to men. However, financial status is also associated with pro-environmental choices, as among the women's group, women with better financial status are the most likely to show greater environmental concern. Essay 3 examines whether Brazilians' environmental engagement is more associated with environmental concern or with environmental knowledge. Through the structural equation model, it was found that both environmental engagement and environmental concern influence the environmental engagement of individuals, but the effect of environmental concern is slightly higher.